The Description of Social Support in Continuing Education to College in Orphanage Children - Tassi, Alfa Daniela; Keraf, M. K. P. Abdi; Benu, Juliana Marlin Y. (Journal of Health and Behavioral Science, 2025)
In continuing education to college, every child needs social support fromthe closest environment, including orphanage children. The purpose of this studywas to obtain an overview of social support in continuing education to college infoster children at 221 GMIT Ebenhaezar Oeba Christian Orphanage. This type ofresearch is qualitative research using interviews as data collection. The number ofparticipants in this study were 10 foster children. Using thematic analysistechniques, this study produced four main themes, namely Constraints inEducation Sustainability, Forms and Sources of Social Support, Impact of Support,and Challenges in Providing Social Support. The results of this study show thatthe social support received by foster children is emotional support, appreciationsupport, instrumental support, and informative support, which is described in 7more specific forms of support. The support comes from the child's closestenvironment, such as caregivers, parents, peers, teachers, and the outsidecommunity.